Production of macrozoobenthos in the estuaries of Primorye - Nickolay V. Kolpakov (Известия ТИНРО, 2015)
Secondary production of macrobenthic communities is evaluated for 14 different-type estuaries in Primorye on the base of 52 surveys conducted in 2007-2013 (922 stations, 2426 samples). Species composition and abundance of macrobenthos in the estuaries depend mostly on water salinity. Three types of estuaries were distinguished: i) polyhaline with prevaled salinity 18-30 ‰ (external and internal estuaries of the rivers Ryazanovka, Barabashevka, Sukhodol, Tumanovka and external estuaries of the rivers Olga and Avvakumovka); ii) mesohaline with salinity 5-18 ‰ (external and internal estuaries of the rivers Tesnaya and Gladkaya, internal estuaries of the rivers Avvakumovka, Kievka, and Partizanskaya, Lake Presnoye and external estuary of the Razdolnaya River); and iii) oligohaline with salinity 0.5-5.0 ‰ (internal estuaries of the rivers Razdolnaya, Artemovka and Lake Solenoye). Mean annual biomass of macrozoobenthos is the lowest (2.8 ± 0.4 gС/m2) in the polyhaline estuaries and the highest in the meso- and oligihaline ones (6.6 ± 3.0 and 7.0 ± 2.5 gС/m2, respectively). Annual production of macrobenthic communities in the estuaries varies from 0.5 to 11.2 gС/m2, with mean values 7.5 ± 1.0 gС/m2 in the polyhaline estuaries, 4.1 ± 1.3 gС/m2 in the mesohaline estuaries, and 2.7 ± 1.4 gС/m2 in the oligohaline estuaries, it is the highest in the polyhaline estuaries and the lowest in the oligohaline ones. The production is formed mainly by gastropods, bivalves, polychaetes and amphipods in the polyhaline estuaries; the same groups and also isopods and amphibiotic insects larvae form the production in the mesohaline estuaries, and bivalves and polychaetes are the main producers in the oligohaline estuaries. Daily production of macrobenthic community has strong seasonal variation with the maximum in July-September and the minimum (sometimes below zero) in May-June and October, i.e. at the beginning and the end of vegetation season. The portion of carnivore macrobenthos production varies from 0.7 to 26.5 % of the total annual production of macrobenthic community, it is the highest in the mesohaline estuaries. It increases from spring to autumn; in the autumn predators have the best feeding because of high abundance of young benthic animals at the bottom of estuaries. Mean annual P/B -ratio is 3.4, 1.1 and 0.4 for the polyhaline, mesohaline and oligohaline estuaries, respectively, that is conditioned by species composition of dominant taxonomic groups. Species composition of bivalve mollusks is the main factor of macrobenthic production variability: brackish clam Corbicula japonica with high biomass (up to 5 kg/m2) and low P/B -ratio (0.4-0.7, mean value ≈ 0.5) dominates in the mesohaline and oligohaline estuaries, while euryhaline marine bivalves as Macoma spp., Potamocorbula amurensis, Laternula marilina , and others dominate in the polyhaline estuaries though their biomass is relatively low (no more than 0.36 kg/m2), their P/B -ratio is 0.8-4.5. Year-to-year variability of macrozoobenthos production is supposedly significant, at least its considerable fluctuations are registered in the Sukhodol estuary (from 4.8 to 11.2 gС/m2 in the 2009-2012). Estuarine macrobenthic communities in Primorye usually have intermediate values of production between those in freshwater and seawater biotopes.